ANALYSIS OF CONSTRUCTIVE CHARACTERISTICS OF THE SUPPLY ZONE SUPPLY CYLINDER OF SPINNING MACHINES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In the article, the main stages of fiber impact in the discretizer drum: supply, discretization, transportation, separation, and then cross-connected transportation with air are carried out.